2012
DOI: 10.3144/expresspolymlett.2012.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection molding parameters on nanofillers dispersion in masterbatch based PP-clay nanocomposites

Abstract: Abstract. The effect of injection molding parameters (screw rotational speed, back pressure, injec-tion flow rate and holding pressure) on the nanofiller dispersion of melt-mixed PP/clay nanocomposites was investigated. The nanocomposites containing 4 wt% clay were obtained by dilution of a PP/clay masterbatch into a PP matrix. The evaluation of the dispersion degree was obtained from dynamic rheological measurements. The storage modulus and complex viscosity exhibit significant dependence on the injection mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
(52 reference statements)
0
21
0
Order By: Relevance
“…Organomontmorillonite (OMMT) is one of the commercial organoclays that has been widely utilized as reinforcing filler in polymer nanocomposites [1][2][3]. Numerous authors have reported on the enhancement in strength and modulus [4][5][6], gas barrier [7] and flame retardant properties [8][9] of polymer/OMMT nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Organomontmorillonite (OMMT) is one of the commercial organoclays that has been widely utilized as reinforcing filler in polymer nanocomposites [1][2][3]. Numerous authors have reported on the enhancement in strength and modulus [4][5][6], gas barrier [7] and flame retardant properties [8][9] of polymer/OMMT nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Even if attempts have been made to use pristine (unmodified) clay [7], modification of clay with organic cations (by cationic exchange with the sodium cations of the mineral) and addition of compatibilizers such as maleic anhydride (MA) are common solutions used to improve the interaction between PP and clay nanoplatelets. Besides, proper choice of processing conditions may further improve clay dispersion [8]. The organic cations used for clay modification are usually alkyl ammonium cations with different chemical structures depending on the considered polymer matrix.…”
mentioning
confidence: 99%
“…Polar interactions are created between the silicate lamella and the hydroxyl groups of the starch [4][5][6]. The dispersion, intercalation and exfoliation of clay, and especially montmorillonite, in PP have also been widely investigated [7][8][9][10][11][12][13][14][15][16][17]. The exfoliation of clay platelets is an uphill task, particularly in non-polar hydrophobic polymers like PP because of the unfavourable enthalpic interaction with the highly hydrophilic clay, which prohibits the diffusion of polymer molecules into the intergallery space.…”
mentioning
confidence: 99%
“…Measured thermal conductivity values are much lower than those ones estimated by rule of mixture approach. The main factor which limits the property improvement of polymer composites is the poor dispersion and the so called segregation effect [8][9][10]. The dispersion is a critical issue mainly for the application of polymer composites with nanofillers [11].…”
Section: Introductionmentioning
confidence: 99%